2019
DOI: 10.1016/j.cub.2018.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Rocking Promotes Sleep in Mice through Rhythmic Stimulation of the Vestibular System

Abstract: Highlights d Rhythmic mechanosensory stimulation (aka rocking) promotes sleep also in the mouse d Linear acceleration applied to the head encodes the rocking stimulus d The rocking effects on sleep are acceleration and time specific d The otolithic organs of the vestibular system mediate the rocking effects on sleep

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
78
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(103 citation statements)
references
References 50 publications
12
78
0
5
Order By: Relevance
“…Local field potentials in the female fly brain were previously shown to differ between daytime and nighttime sleep (van Alphen et al, 2013) suggesting qualitative differences between them, with daytime sleep deemed to be lighter. Our studies are consistent with previous studies that showed that rocking can induce sleep in humans and mice (Perrault et al, 2019; Kompotis et al, 2019; Bayer et al, 2011). Orbital motion induced quiescence is completely reversible by pharmacological and behavioural interventions (Figure 3) and thus qualifies this criterion for sleep.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Local field potentials in the female fly brain were previously shown to differ between daytime and nighttime sleep (van Alphen et al, 2013) suggesting qualitative differences between them, with daytime sleep deemed to be lighter. Our studies are consistent with previous studies that showed that rocking can induce sleep in humans and mice (Perrault et al, 2019; Kompotis et al, 2019; Bayer et al, 2011). Orbital motion induced quiescence is completely reversible by pharmacological and behavioural interventions (Figure 3) and thus qualifies this criterion for sleep.…”
Section: Discussionsupporting
confidence: 93%
“…Based on previous studies of mammals including humans where rocking motion was found to induce daytime sleep (Kompotis et al, 2019; Perrault et al, 2019; Bayer et al, 2011) we set out to examine the effect of sustained orbital motion on flies. Here we report for the first time that gentle orbital motion (Figure 1a) induces sleep in D. melanogaster .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to the wide range of vibration frequency used in our studies, human and mouse studies investigating the effects of rocking on adult sleep used a narrow range of frequencies (0.16 -1.5 Hz) (Bayer et al, 2011;Kompotis et al, 2019;Perrault et al, 2019). Nevertheless, they found variable results in terms of the specific sleep parameters that were affected (e.g., sleep duration and sleep latency).…”
Section: Discussionmentioning
confidence: 92%
“…Anecdotal observations suggest that babies sleep better when gently rocked or bounced and people tend to fall asleep during long car rides. Several experimental studies have confirmed that rocking promotes sleep in infants, adult humans, and mice (Bayer et al, 2011;Kompotis et al, 2019;Korner et al, 1978;Perrault et al, 2019). Yet the underlying mechanisms are not well understood.…”
Section: Introductionmentioning
confidence: 99%